Implementasi Profile Matching untuk menentukan Tempat Kerja yang sesuai dengan Kompetensi bagi Lulusan STMIK Pelita Nusantara Medan - Taufik, Insan; Fitra, Awaludin (MEANS (Media Informasi Analisa dan Sistem), 2019)
The number of graduates of computer science colleges who work not in accordance with their competencies, can be caused by choosing the wrong place to work, but it is undeniable that many graduates do not work according to their competence because of difficulties in finding a work place due to not having a lot of references to the appropriate workplace with competence. The purpose of the research is in addition to continuing previous research, is to make it easier for students to find out the competencies they have while suggesting workplaces that are in accordance with the competencies of the graduates. Indirectly researchers want to avoid the formation of thinking to the community that college at university is not able to facilitate someone in finding work, so that people will be more motivated to continue learning and achievement especially in college